Prevalence of Nephrolithiasis in 7-11 year-old Students: A Multicenter Study - Pourbakhtyaran, Elham; Mohkam, Masoumeh; Karimi, Abdollah; Akhavan- Sepahi, Mohsen (Journal of Pediatric Nephrology, 2019)
Introduction: Renal diseases can be asymptomatic even in progressive disorders; therefore, detecting urine and ultrasound abnormalities may help facilitate early diagnosis and prevention of renal diseases. This study was conducted to investigate random urine parameters and urinary system ultrasonography findings in 7-11 year-old students. Materials and Methods: Healthy students from Tehran and Qom, Iran were enrolled in a prospective descriptive study and their sex, age, weight, height, and BMI were measured. Then, a fresh clean urine sample was collected and ultrasonography of the urinary tract was done. The urine specimen was tested for urine Ca/Cr, urine oxalate/Cr, and urine citrate/Cr. Results: Of 932 students, 47.9% were female and 52.1% were male. The age range of the students was 7-11 years with a mean age of9.08 years. A history of renal disease and UTI was positive in 1.1% and 9.9% of the students, respectively. Ultrasound was normal in78% and abnormal in 22% of the students. Abnormal findings included hydronephrosis in 1.1%, fullness of the urinary tract in 0.1%, urinary system duplication in 3%, urolithiases in 0.7%, decreased kidney size in 0.4%, increased bladder thickness in 8.9%, and other abnormal findings in 7.8% of the subjects. Abnormal urine findings included hypercalciuria, in 10.9%, urine hyperuricosuria in 5.4%, urine hyperoxaluria in 12.8%, and hypocitraturia in 96.9% of the students. Conclusions: According to the results, nephrolithiasis may be due to hyperoxaluria, hypercalciuria, and hyperuricosuria in a normal population. Genetics and nutrition are more important risk factors. Therefore, some nutritional interventions for decreasing urine oxalate, calcium, and uric acid may be beneficial. Keywords: Urinalysis; Ultrasonography; Hypercalciuria; Hyperuricosuria; Hyperoxaluria; Child.